1996
DOI: 10.1016/0029-7844(95)00376-2
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasma urealyticum Infection of the Placenta in Pregnancies That Ended Prematurely

Abstract: Ureaplasma urealyticum infection is associated with premature onset of labor and with increasing duration of time between rupture of membranes and delivery. Eradication of ureaplasmas from the urogenital tract of women and their partners, ideally before conception, should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…Robertson et al (42) found a connection between colonisation of vagina with U. urealyticum and premature labor, and Donders et al (7) found that bacterial vaginosis and presence of U. urealyticum and M. hominis in the vagina were associated with an increased risk of early miscarriage. U. urealyticum has also been found in the placenta, associated to perinatal morbidity and mortality and preterm labor (43,44). However, colonisation of the uterine cervix with U. urealyticum is quite common in women who did not experience any problem during pregnancy (45), so its possible role in induction of miscarriage is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Robertson et al (42) found a connection between colonisation of vagina with U. urealyticum and premature labor, and Donders et al (7) found that bacterial vaginosis and presence of U. urealyticum and M. hominis in the vagina were associated with an increased risk of early miscarriage. U. urealyticum has also been found in the placenta, associated to perinatal morbidity and mortality and preterm labor (43,44). However, colonisation of the uterine cervix with U. urealyticum is quite common in women who did not experience any problem during pregnancy (45), so its possible role in induction of miscarriage is questionable.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial pathogens that are most frequently isolated in cases of chorioamnionitis include the human Ureaplasma species (Ureaplasma parvum and Ureaplasma urealyticum), Fusobacterium spp., Streptococcus spp., and, less frequently, Gardnerella spp., Mycoplasma spp., and Bacteroides spp. (1,62,120,(122)(123)(124). Other studies have identified that the sexually transmitted pathogens Chlamydia trachomatis and Neisseria gonorrhoeae, along with the uropathogen E. coli and yeast Candida spp., are also infrequently associated with chorioamnionitis (122,(125)(126)(127)(128).…”
Section: Causative Agents Of Chorioamnionitismentioning
confidence: 99%
“…is not reliably predictive of preterm labor (42), but there is an association when it is present in the amniotic fluid or placenta (43,125,163,339,342). Two recent reviews of antibiotic trials involving treatment of pregnant women who were culture positive for ureaplasmas in their vaginas concluded that there is insufficient evidence to recommend administration of antibiotics to women with ureaplasmas in the vagina to prevent preterm birth (148,229).…”
Section: Chorioamnionitis Spontaneous Abortion and Preterm Labormentioning
confidence: 99%